Demografía y genética de la población amerindia Guaymí de Limoncito, Costa Rica - Barrantes, Ramiro (1981)
A demographic and genetic study of the Guaymi Amerindian population at Limoncito, Coto Brus, Costa Rica, showed that 47% of the population is between the ages of 0 and 14 and 35% between 15 and 44. The sex ratio is 91, which is evidence of a greater number of females. Forty percent of the couples come from Panama, but the filial generation (98%) was born in Limoncito. Emigration is very low. The selective potential is relatively high (0.94), with the mortality component predominating. Endogamy and the inbreeding coefficient have high values and polyginy is common. The effective and reproductive size of the population is small. Evolutionary implications of the results are discussed.